The influence of the reward culture on client-led service innovation in academic libraries of Uganda - Lwanga, Elizabeth Namale Kawuma; Ngulube, Patrick (Emerald, 2024)
Purpose Client-led service innovation has gained currency in academic libraries owing to ever-shifting client preferences. Library clients are interested in determining which services libraries should offer to meet their information needs. Several studies have investigated service innovation or improvement in libraries with an emphasis on client involvement. However, it is not clear whether the reward culture influences client-focused service innovation in the context of Uganda. Design/methodology/approach This multiple-case study triangulated data from a survey of 80 staff members, three semi-structured interviews conducted with three library heads, and data from institutional documents. Data were analysed quantitatively and qualitatively. Findings The results indicated that the financial reward culture did not influence client-led service innovation in any way; instead, non-financial rewards had an impact. Therefore, library managers need to appreciate that clients are no longer interested in financial rewards, but rather in non-financial rewards that have enduring value. Originality/value The study underscores the importance of client-led services in an information environment that has been invaded by industry 4.0 and calls upon librarians to use the opportunity to provide innovative services.